2017
DOI: 10.3389/fnbeh.2017.00139
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Changes Over Time Following Ayahuasca Exposure in Zebrafish

Abstract: The combined infusion of Banisteriopsis caapi stem and Psychotria viridis leaves, known as ayahuasca, has been used for centuries by indigenous tribes. The infusion is rich in N, N-dimethyltryptamine (DMT) and monoamine oxidase inhibitors, with properties similar to those of serotonin. Despite substantial progress in the development of new drugs to treat anxiety and depression, current treatments have several limitations. Alternative drugs, such as ayahuasca, may shed light on these disorders. Here, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 87 publications
0
21
0
Order By: Relevance
“…***p < 0.001, **p < 0.01, and *p < 0.05 in comparison to saline/saline group. ++p < 0.01 and +p < 0.05 in compared with the saline/harmaline group neurotrophic factor (BDNF) (Abelaira et al 2013;Dos Santos et al 2016a, b;Moloudizargari et al 2013;Savoldi et al 2017;Splettstoesser et al 2005). So it can be concluded that harmaline induced antidepressant-and anxiolytic-like effects in the ARS mice by stimulation of neurogenesis, induction of neuroprotective properties, and inhibition of MAO-A as well as enhancement of serotonin concentrations in the brain (Biradar et al 2013;Dos Santos et al 2016a;Morales-Garcia et al 2017).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…***p < 0.001, **p < 0.01, and *p < 0.05 in comparison to saline/saline group. ++p < 0.01 and +p < 0.05 in compared with the saline/harmaline group neurotrophic factor (BDNF) (Abelaira et al 2013;Dos Santos et al 2016a, b;Moloudizargari et al 2013;Savoldi et al 2017;Splettstoesser et al 2005). So it can be concluded that harmaline induced antidepressant-and anxiolytic-like effects in the ARS mice by stimulation of neurogenesis, induction of neuroprotective properties, and inhibition of MAO-A as well as enhancement of serotonin concentrations in the brain (Biradar et al 2013;Dos Santos et al 2016a;Morales-Garcia et al 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Harmaline commonly identified to provoke motor variations via activation of cells in the inferior olive (Hilber and Chapillon 2005 ). Besides, studies revealed that harmaline has antidepressive and anxiolytic properties that seem to be mediated by MAO inhibition and modulation of serotonin (5-HT), benzodiazepine, and dopamine receptors (Abelaira et al 2013 ; Dos Santos et al 2016a ; Dos Santos et al 2016b ; Savoldi et al 2017 ; Splettstoesser et al 2005 ). Interestingly, harmaline is endogenously produced in human and animal tissues as a low-molecular-weight product of secondary metabolism (Li et al 2017b , c ; Moloudizargari et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The final batch was stored in glass bottles in a refrigerator. The main ayahuasca alkaloids were quantified at the beginning of the study using mass spectroscopy, resulting in values of 0.36±0.01 mg/mL DMT, 1.86±0.11 mg/mL harmine, 0.24±0.03 mg/mL harmaline, and 0.20±0.05 mg/mL THH 4,18. The tea used in this study was the same as that used in previous studies 4,18…”
Section: Methodsmentioning
confidence: 99%
“…Finally, predictive validity shows how animal performance predicts the condition being tested. In Brazil, numerous neuroscience and behavioral studies have used the zebrafish as a model to understand the effects of coffee, 56,57 ayahuasca, 58,59 and alcohol. [60][61][62][63] This field is gaining importance worldwide, and new research partnerships are being established based on the know-how gained by Brazilian researchers.…”
Section: Research Areasmentioning
confidence: 99%